Rebound effect after topical treatment with propranolol - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 1-month-old child was first observed due to the presence of a precursor of hemangioma in the right frontal and palpebral region (Fig. 1). Given the superficiality of the lesion we decided to treat the child with topical 1% propranolol in fat-based lotion, two times a day. After 2 months of therapy, the precursor was almost completely regressed (Fig. 2), but we decided to continue topical treatment with 1% propranolol until the age of five months. At a control visit carried out one month after the suspension, the precursor returned evident (Fig. 3). With the parents we decided to monitor the precursor clinically without any therapy; at the age of 1 year, the precursor had become even more evident (Fig. 4), leading to the final diagnosis of rebound effect after topical therapy with propranolol.